2018
DOI: 10.1111/exd.13484
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet exacerbates imiquimod‐induced psoriasis‐like dermatitis in mice

Abstract: Psoriasis, a chronic inflammatory skin disease, is closely related to systemic metabolism. An elevated body mass index (BMI) is a risk factor for psoriasis; inflammasomes are activated by adipose tissue macrophages in obese subjects. We hypothesized that hyperlipidaemia is involved in the pathogenesis of psoriasis and examined the role of a high-fat diet (HFD) in the development of psoriasis in imiquimod (IMQ)-treated mice. The body weight and serum level of cholesterol were significantly higher in mice fed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
2
17
1
Order By: Relevance
“…Except for direct induction, all models are characterized by high expense, long-term, high operative difficulty and low throughput which are not applicable for preclinical drug validation and screening [ 13 , 14 ]. IMQ-induced psoriasis is a classical direct induction model and widely used in fundamental research and anti-psoriatic drug evaluation [ 20 , 24 , 26 , 27 ]; there is also another direct induction model which intradermal inject IL23 in mice ear and induced local psoriasis like pathological change [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for direct induction, all models are characterized by high expense, long-term, high operative difficulty and low throughput which are not applicable for preclinical drug validation and screening [ 13 , 14 ]. IMQ-induced psoriasis is a classical direct induction model and widely used in fundamental research and anti-psoriatic drug evaluation [ 20 , 24 , 26 , 27 ]; there is also another direct induction model which intradermal inject IL23 in mice ear and induced local psoriasis like pathological change [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participation of IL17A signaling in IMQ model has been revealed by previous reports, IMQ induced epidermal expression of IL17A during 6-day modelling, which is attributed to Th17 cell mobilization [ 22 ]; as a newly discovered receptor for IL17A, IL17RD is also determined for IMQ-induced psoriatic inflammation [ 23 ]; in another study, blocking IL17A signaling by knocking out IL17 Receptor A (IL17RA) diminishes the severity of IMQ induced pathological change [ 19 ]. IL17A expression is also positively correlated with the disease progression of the model: induction of IL17A by high-fat diet augments severity of disease, while impairing the IL17A-producing Th17 cells by vitamin D analogue exerts anti-psoriatic effect [ 20 , 21 ]. Our study additionally revealed the involvement of IL17A in the development of IMQ-induced disease: despite of the slow change of basal level IL17A during the 7 day course of experiment, IMQ induced sharp IL17A expression after application, and the downstream signaling was correspondingly activated.…”
Section: Discussionmentioning
confidence: 99%
“…These nutrition-dependent effects translated into exacerbated EAE via the expansion of pathogenic T H 1 and/or T H 17 cell populations (122). Furthermore, a diet high in saturated fatty acids is sufficient to exacerbate psoriatic skin inflammation independent of obesity (123) and this effect seems to be linked to an augmented T H 17 response in the skin (124). Given that weight loss through diet adaptation can improve pre-existing psoriasis and prevent the onset of psoriasis in obese individuals it can be speculated that the beneficial effects thereof are at least in part mediated through an altered cross-talk between systemic metabolism and local T cell function (125).…”
Section: T Cell Metabolism In Inflammatory Skin Diseasementioning
confidence: 99%
“…Intriguingly, a recent study indicated that a high-dietary-fat diet exacerbates psoriatic skin inflammation independent of obesity (Herbert et al, 2018). Another study, using different chow recipes, also Western Diet Exacerbates Psoriasis concluded that high dietary fats exacerbate IMQ-induced psoriasis-like dermatitis in mice (Higashi et al, 2018). Despite being termed high-fat diets by their authors, these two studies used diets that were not only rich in fat, but also had a high content of simple sugars, bearing considerable similarity to the WD used in our studies ( Supplementary Table 1 online).…”
mentioning
confidence: 99%